Aplicação de coberturas comestíveis a base de fécula de mandioca, cera de abelha e extrato de romã na conservação de queijo tipo coalho - Freire, Bárbara Camila Firmino (Universidade Federal Rural do Semi-Árido, 2019)
The curd cheese is a dairy product with high expression in the Northeast of Brazil, where it is very produced and consumed. However, the inherent characteristics of this product, as well as the lack of standardization in production, tend to compromise its quality and safety. Thus, conservation methods are necessary to maintain its quality, and, currently, there is a bigger search for natural alternatives in this area of research. As an example, the use of edible coatings obtained by the exploration of biopolymers and bioactive compounds. The objective of this study was to produce an edible cover based on cassava starch, beeswax and pomegranate extract and evaluate its efficiency in the quality of curd cheese. Initially, different types of films and covers were produced to characterize the properties and application in cheese pieces, respectively. The films did not present differences between the treatments, except in the color, microstructure and mechanical properties, being the film added of extract of pomegranate and beeswax more resistant to breaking and flexible. After the cheese was produced and the coverings were applied, the sensorial analysis was carried out, demonstrating a good acceptance by the tasters. In the evaluation of the quality and shelf life, samples stored under refrigeration (7±1° C) over 15 days obtained satisfactory results in the reduction of deteriorants, especially on aerobic mesophilic bacteria in all treatments. In physicochemistry, the coatings reduced the acidity of the samples, remaining statistically relevant until the ninth day of analysis and without interfering with the color of the cheeses. From the data obtained, it is concluded that the natural coverings appear as an alternative in the conservation of rennet cheese, with the best results observed using the cassava starch, pomegranate extract and beeswax coverage
Keywords: Biopolímeros; Produto lácteo; Análises de alimentos; Conservação; Biopolymers; Dairy product; Food analysis; Conservation; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE